Ultrasonic fatigue test at cryogenic temperatures on SUS304L by cold rolling ratio for LNG carriers. (May 2020) - Shim, Hyun-Bo; Nahm, Seung-Hoon; Cho, In-Sik; Suh, Chang-Min
Highlights: This study examined the effects of cold rolling ratio and cryogenic temperatures on the mechanical properties of a 1.5 mm SUS304L sheet. Moreover, to identify the effect of cryogenic temperatures, very high cycle fatigue (VHCF) characteristics were obtained at −162 °C and −196 °C, using the ultrasonic fatigue tester. The increase in the fatigue limit caused by to the cold rolling and cryogenic temperatures in the results of the UFT is similar to the tendency of increased tensile strength and dynamic elastic modulus. Abstract: This study examined the effects of cold rolling ratio and cryogenic temperatures on the mechanical properties of a 1.5 mm SUS304L sheet, the original material used in membrane-type liquefied natural gas (LNG) storage tanks. The original sheet was cold rolled to reduce its thickness in order to examine the effect of cold rolling ratio. And to identify the effect of cryogenic temperatures, very high cycle fatigue (VHCF) characteristics were obtained at −162 °C, using the ultrasonic fatigue tester. The fatigue limit of a 1.5 mm specimen, measured at −162 °C in the ultrasonic fatigue test (UFT) was 252 MPa, while that of 1.3 mm and 1.1 mm cold rolled specimens was 503 MPa and 597 MPa, up by about 99.6% and 137% respectively. The fatigue limit of 1.3 mm and 1.1 mm cold rolled specimens measured at −196 °C was 550 MPa and 690 MPa, up by about 88.4% and 136.3% respectively. As such, the fatigue strength of the cold rolled specimen in the UFT tend to increase in a nearly linear manner, compared to that of the original material, as the cold rolling ratio and the effect of cryogenic temperatures.